Thermal radiation and chemical reaction effect on Casson Fluid, Heat and Mass Transfer over a Permeable Vertical Stretching Surface - Y. Hari Krishna, Hari Krishna; P. , Bindu (International Journal of Psychosocial Rehabilitation, 2020)
This article studies Casson fluid flow, heat, and mass transfer over a permeable vertical stretching surface, considering the effects of magnetic field, thermal radiation, and chemical reactions. After applying the suitable similarity transforms, the governing equations of flow are solved numerically by the shooting technique along with a 6th-order Runge-Kutta iteration scheme with the MATLAB package. The impacts of various values of parameters on the velocity, temperature, and concentration distributions are discussed through graphs. Expressions for shear stress, rate of heat transfer, and rate of mass transfer are analyzed and given in tabular form.